2019
DOI: 10.3390/ijms20153691
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle-Induced Differentiation of Neural Stem Progenitor Cells

Abstract: Neural stem progenitor cells (NSPCs) from E13.5 mouse embryos can be maintained in culture under proliferating conditions. Upon growth-factor removal, they may differentiate toward either neuronal or glial phenotypes or both. Exosomes are small extracellular vesicles that are part of the cell secretome; they may contain and deliver both proteins and genetic material and thus play a role in cell–cell communication, guide axonal growth, modulate synaptic activity and regulate peripheral nerve regeneration. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…During early development, neural stem cells (NSCs) release EVs that affect neurogenesis and appear to regulate the switch between the neurogenic and gliogenic fate by delivering micro‐RNAs. The influence on NSC fate, however, may differ depending on the regional origin or the specific developmental state of the NSCs 12,13 . In addition to their impact on neurogenesis, NSC‐EVs exhibit immunomodulatory activity turning them to promising candidates for application in regenerative therapies of brain disease or injuries 14,15 …”
Section: Cellular Routes Of Neural Evsmentioning
confidence: 99%
“…During early development, neural stem cells (NSCs) release EVs that affect neurogenesis and appear to regulate the switch between the neurogenic and gliogenic fate by delivering micro‐RNAs. The influence on NSC fate, however, may differ depending on the regional origin or the specific developmental state of the NSCs 12,13 . In addition to their impact on neurogenesis, NSC‐EVs exhibit immunomodulatory activity turning them to promising candidates for application in regenerative therapies of brain disease or injuries 14,15 …”
Section: Cellular Routes Of Neural Evsmentioning
confidence: 99%
“…They became almost an obligatory part of the neuroscience toolbox, so they are used in basic research [ 132 ] and in new translational strategies [ 133 , 134 ]. Their biological properties mostly depend on secreting intrinsic and extrinsic factors and molecules by which they control neural development and recovery [ 135 ]. These factors and molecules include: growth factors, proteins, miRNA and vesicles, which when secreted are known as extracellular vesicles.…”
Section: Type and Role Of Evsmentioning
confidence: 99%
“…In particular, by microarray analysis, it was found that these exosomes contained high amounts of miR-125b (already known to play a role in neurogenesis) [224]. By the way, neural stem progenitor cells (NSPCs) were found to release EVs too, both in proliferating and differentiating conditions; however, EVs derived from differentiating NSPCs induce differentiation in a dose-dependent manner, and in a cell-type specific direction-EVs from astrocyte-like cells can indeed drive NSPC differentiation toward glial lineage [225].…”
Section: Synaptic Plasticity: the Possible Role Of Evs And Their Cargoesmentioning
confidence: 99%